Encouraging exercise in older adults: advice for nurses. - Palmer, Sarah Jane (British Journal of Community Nursing, 2020)
Physical activity is well documented to contribute to better mental and physical wellbeing in older adults. Physical exercise also plays a part in falls prevention, thus reducing fear of injury when exercising. Motivational interviewing to encourage exercise among older adults should be assertive yet kind, with the provision of an appropriately trained staff member, convenient fitness facilities to access and consideration of cost. Facilitators and barriers affect an older person's motivation to engage in physical exercise. Barriers include cost, physical barriers, fear of injury, low motivation, dislike of exercise, locality of the service and more. In this article, the available evidence is examined to discuss the subjects of motivational interviewing, facilitators and barriers to exercise and ways to overcome the latter.